Effects of Compudose® implants on performance carcass, meat quality traits and serum testosterone in young boars - Timmis, T.; Dikeman, Michael E.; Hunt, Melvin C.; Highfill, G.; Stevenson, Jeffrey S.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Implanting boar pigs at 100 lb with 24 mg of Compudose 200® (estradiol 17β) had no significant effect on "boar odor" in meat, rate of gain, feed efficiency, carcass leanness or meat quality traits. The presence of a 7 to 8 mo old gilt in the pen decreased rate of growth in both control and implanted boars, but contrary to our expectations did not increase the incidence of “boar odor".
Keywords: Swine; Compudose; Carcass; Meat quality; Serum; Testosterone